Youth and politics in the change of an era - Tanaka, Martín (1993)
What is the relationship between youth and politics? Is it a relevant topic? In what sense is it important to ask about the relationship between youth and politics? What can youth contribute to national politics? In this work we will address the relationship between youth and politics, affirming the importance of this theme, despite the notorious "depoliticization" of young people. We do it not because young people clearly constitute a social or political actor, but because they contain identities, values ​​and aspirations that allow us to understand the emergence of a new Peru, which requires and will give rise to new political relations.